Extracellular vesicles therapy: opportunities, mechanisms and perspectives - F. S. Velikonivtsev; A. S. Golovkin (Российский кардиологический журнал)
Extracellular vesicles are biological membrane-coated objects with size less then 1000 nm. They can contain variety of biologically active molecules (such as proteins, miRNA, mRNA, DNA etc.) and also are able to provide intercellular communications and implement lots if biological functions. Now possibilities of using extracellular vesicles for therapeutic approaches against various diseases and pathological conditions are rapidly discovered. In the most of cases mesenchymal stem cells are the sources of extracellular vesicles and miRNAs which vesicles transport are considered to be causable agents of their activities. In-vitro studies show that extracellular vesicles provide anti-inflammatory, anti-apoptotic activities and can stimulate angiogenesis and regeneration. Performed studies which were analyzed and structurized by us in this review demonstrate current perspectives for clinical use of extracellular vesicles in the therapy of such clinical conditions as oxidative stress, ischemia-reperfusion injury, tumor growth etc.